Adolescents' Retributive and Restorative Orientations in Response to Intergroup Harms in Schools. (17th July 2022) - Pareja Conto, Laura; Restrepo, Angelica; Recchia, Holly; Velez, Gabriel; Wainryb, Cecilia
Abstract : This mixed‐methods study examined how adolescents understand and evaluate different ways to address intergroup harms in schools. In individual interviews, 77 adolescents ( M age = 16.49 years; 39 girls, 38 boys) in Bogotá, Colombia, responded to hypothetical vignettes wherein a rival group at school engaged in a transgression against their group. Adolescents reported that students who were harmed should and would talk to school authorities, but also noted they would likely retaliate. In terms of teacher‐sanctioned responses to harm, youth endorsed compensation most strongly, followed by apologies, and rated suspension least positively. Youths' explanations for their endorsement of different disciplinary practices reflected varied concerns, including their perceptions of how justice is best achieved and how restoration could be attained.